Hands in Cont(r)act: The Resiliency of Business Handshakes in Pandemic Culture. Issue 2 (August 2019) - Hamilton, Sheryl N.
Abstract: This article examines the persistence of the handshake in business circles despite its implication in the spread of communicable disease in contemporary pandemic culture. An examination of business etiquette discourse suggests that even during disease outbreaks or flu season, the business handshake remains an important visual and haptic legal gesture. While it may no longer produce a binding legal contract, it stages the parties as contractable subjects, as claiming the status of autonomous individuals committed to defining their intersubjective relationship through the norms of contract. The business handshake thus operates as a cultural site for the complex interaction of bodies and law, and the production of masculine, haptic-legal subjectivity. Résumé: Cet article examine la persistance de la pratique de la poignée de main dans les milieux d'affaires malgré son implication dans la propagation des maladies transmissibles dans la culture pandémique contemporaine. Un examen du discours sur l'étiquette des affaires suggère que même au plus fort des épidémies ou pendant la saison de la grippe, la poignée de main commerciale demeure un geste juridique visuel et haptique important. Bien que la poignée de main ne produise plus de contrat juridiquement contraignant, elle présente les parties en tant que sujets contractuels qui revendiquent le statut d'individus autonomes engagés à définir leur relation intersubjective à travers les normes du contrat. La poignée de main dans les milieux d'affaires opère comme un espace culturel pour l'interaction complexe des corps et du droit ainsi que pour la production d'une subjectivité masculine et hapto-juridique.